Comparative effects of five polymethoxyflavones purified from Citrus tangerina on inflammation and cancer - Chen, Qiyang; Gu, Yue; Tan, Chun; Sundararajan, Balasubramani; Li, Zhenqing; Wang, Dan; Zhou, Zhiqin (Frontiers in Nutrition, 2022)
Although the Citrus tangerina cultivar ‘Dahongpao’ (CTD) has been established as a rich source of polymethoxyflavones (PMFs) with anti-inflammatory and anti-cancer properties, their individual effects on cellular signaling remain to be elucidated. In this study, five major PMFs from the peel of CTD were isolated, including sinensetin, tetramethyl-O-scutellarin (5,6,7,4′-tetramethoxyflavone), nobiletin (5,6,7,8,3′, 4′-hexamethoxyflavone), tangeretin (5,6,7,8,4′-pentamethoxyflavone), and 5-demethylnobiletin (5-OH-6,7,8,3′,4′-pentamethoxyflavone). These PMFs were found to significantly (p<0.05) inhibit the production of NO and biomarkers of chronic inflammation (TNF-α and IL-6). Additionally, they effectively suppressed mRNA biomarkers of acute inflammation (Cox-2 and iNOS), and to varying degrees promoted the activation of anti-inflammatory cytokines (IL-4, IL-13, TNF-β, and IL-10). Among the five PMFs, tangeretin was found to have a considerable anti-proliferative effect on tumor cell lines (PC-3 and DU145) and synergistically enhanced the cytotoxicity of mitoxantrone, partially via activation of the PTEN/AKT pathway. The findings of this study provide valuable insights into the activity of different PMF monomers and advance the understanding of the roles of PMFs in promoting apoptotic and anti-cancer effects.